Variability of Phenolic and Volatile Compounds in Virgin Olive Oil from Leccino and Istarska Bjelica Cultivars in Relation to Their Fruit Mixtures - Olivera Koprivnjak; Valerija Majetić; Karolina Brkić Bubola; Urška Kosić (Food Technology and Biotechnology, 2012)
Phenolic and volatile compounds are closely related to valuable gastronomic and nutritional properties, as well as oxidative stability of virgin olive oil. Since biochemical synthesis and transformation of these compounds during olive processing depend on the activity of endogenous enzymes, which are partially influenced by genetic factors, mixtures of different cultivars could have either a synergistic or antagonistic effect on phenolic and volatile compounds in the resulting oil. In this context, two specific cultivars from the Istrian peninsula, Leccino (L) and Istarska bjelica (B), were selected. Two monovarietal fruit samples (L100 and B100) and four mixtures in the following mass ratios: L/B=80:20, L/B=60:40, L/B=40:60 and L/B=20:80 were prepared. The mass fraction of total phenols was determined colourimetrically, while C6 and C5 volatiles from lipoxygenase pathway were determined by headspace solid-phase microextraction-gas chromatography. Mass fraction of total phenols in the oil samples from fruit mixtures changed linearly from (199.5±7.2) in Leccino to (642.0±61.7) mg/kg in Istarska bjelica, in a strict correlation with fruit mass ratio of the two cultivars. Leccino monovarietal samples had statistically higher values (p≤0.05) of C6 aldehydes ((15.32±1.69) vs. (10.91±0.62) mg/kg) and C6 alcohols ((2.96±0.98) vs. (0.17±0.05) mg/kg), but lower values of C5 compounds ((0.77±0.12) vs. (0.96±0.05) mg/kg) compared to Istarska bjelica samples. Volatiles having a direct contribution to the oil aroma (odour activity value >1.0) were 1-penten-3-one (84–201), E-2-hexenal (26–42), hexanal (1.8–2.4) and Z-2-penten-1-ol (1.3–2.6). A significant synergistic effect was observed for C6 aldehydes in the case of L/B=40:60 fruit mixture. The addition of Istarska bjelica to Leccino fruits caused a significant antagonistic effect on C6 alcohols, but no significant deviations from the expected values were found in the case of C6 esters and C5 compounds. Results suggest that fruit combinations of two chosen cultivars in olive processing offer interesting possibilities for targeted modulation of phenolic and volatile compounds in virgin olive oil, and consequently, their sensory and nutritional characteristics.